Subsequent measurement of property, plant and equipment in hotel companies in the Republic of Serbia and the Republic of Croatia - Marko Milašinović; Vladimir Obradović; Nemanja Karapavlović (Anali Ekonomskog fakulteta u Subotici, 2022)
The aim of this paper is to consider the practice of subsequent measurement of property, plant and equipment in hotel companies in the Republic of Serbia and the Republic of Croatia, i.e., to determine whether the preparers of financial statements make greater use of the historical cost model or the model based on fair value. The sample consists of 220 hotel companies in the Republic of Serbia and the Republic of Croatia, observing their financial reports for 2019. The research reveals that most hotel companies in both countries subsequently measure owner-occupied property and plant and equipment according to the historical cost model. Hotel companies in Serbia most often apply the fair value model for subsequent measurement of investment property, while hotel companies in Croatia most often apply the historical cost model in the same context. We also find that a large number of hotel companies in the observed countries do not disclose the basis for subsequent measurement of property (including investment), plant and equipment in the notes to their financial statements, which means that the quality of financial reporting on those assets in the hotel companies should be improved.